Anesthesia preoperative evaluation clinic (APEC) restructuring plan for improving the quality of surgical patient flow - Alboim, Carolina; Teixeira, Alice Becker; Soares, Luciana Eltz; Machado, Vanda Regina; Stefani, Luciana Cadore (Clinical and Biomedical Research, 2018)
Introduction: Anesthesia preoperative evaluation clinics (APECs) are useful for high-risk surgical patient care, as they improve perioperative outcomes and optimize patient care flow. At Hospital de Clínicas de Porto Alegre, APEC assesses 20% of all patients undergoing surgery, showing the importance of implementing strategies to improve outpatient clinic efficiency by prioritizing high-risk patients. Methods: Using a specific quality management tool for process improvement (PDCA, which stands for Plan/Do/Check/Act), new protocols were developed for patient referral and preoperative evaluation. Clinical staff was trained in the new routines, and an electronic screening system for patient referral was adopted. Data on patient profiles, referring surgical specialties, type of surgery, and waiting times for appointment and surgical procedure were compared before and after the intervention. Results: APEC performed 1,286 appointments between 2013 and 2016, including 733 pre-intervention and 553 post-intervention. There was a significant decrease in the appointments for patients undergoing minor surgery and an increase in the appointments for those undergoing major surgery. The waiting time between referral to APEC and first APEC appointment reduced from 46 to 16 days. In addition, there was an increase in vascular, orthopedic, and urology referrals, as well as a reduction in ophthalmology and general surgery referrals. Conclusion: The PDCA method assisted with conceiving, executing, and monitoring the implemented strategies for changing the profile of patients evaluated at APEC. The major challenge is to measure the long-term impact of this intervention and expand care through specific strategies for surgical specialties and procedures. KEYWORDS: Preanesthesia evaluation; preoperative evaluation; preoperative stratification; risk stratification